Utilizing T-cell Activation Signals 1, 2, and 3 for Tumor-infiltrating Lymphocytes (TIL) Expansion: The Advantage Over the Sole Use of Interleukin-2 in Cutaneous and Uveal Melanoma. Issue 9 (November 2018) - Tavera, René J.; Forget, Marie-Andrée; Kim, Young Uk; Sakellariou-Thompson, Donastas; Creasy, Caitlin A.; Bhatta, Ankit; Fulbright, Orenthial J.; Ramachandran, Renjith; Thorsen, Shawne T.; Flores, Esteban; Wahl, Arely; Gonzalez, Audrey M.; et al.
Abstract : In this study, we address one of the major critiques for tumor-infiltrating lymphocyte (TIL) therapy—the time needed for proper expansion of a suitable product. We postulated that T-cell receptor activation in the first phase of expansion combined with an agonistic stimulation of CD137/4-1BB and interleukin-2 would favor preferential expansion of CD8 + TIL. Indeed, this novel 3-signal approach for optimal T-cell activation resulted in faster and more consistent expansion of CD8 + CD3 + TIL. This new method allowed for successful expansion of TIL from cutaneous and uveal melanoma tumors in 100% of the cultures in <3 weeks. Finally, providing the 3 signals attributed to optimal T-cell activation led to expansion of TIL capable of recognizing their tumor counterpart in cutaneous and uveal melanoma. This new methodology for the initial phase of TIL expansion brings a new opportunity for translation of TIL therapy in challenging malignancies such as uveal melanoma. Abstract : Supplemental Digital Content is available in the text.